2016
DOI: 10.1139/gen-2015-0212
|View full text |Cite
|
Sign up to set email alerts
|

Linking adults and immatures of South African marine fishes

Abstract: Abstract:The early life-history stages of fishes are poorly known, impeding acquisition of the identifications needed to monitor larval recruitment and year-class strength. A comprehensive database of COI sequences, linked to authoritatively identified voucher specimens, promises to change this situation, representing a significant advance for fisheries science. Barcode records were obtained from 2526 early larvae and pelagic eggs of fishes collected on the inshore shelf within 5 km of the KwaZulu-Natal coast,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 36 publications
1
37
0
1
Order By: Relevance
“…From this study we observed that the inter-specific divergence varied from 7.4 to 10.8% in Squatina with a minimum intraspecific distance of 1.3% in S. africana. The neighbor joining network showed 8 and 9 mutation steps between the present sample (KY497255) and S. africana (HQ945896 and HQ945905) from Tugela Deep (Steinke et al, 2016) and 15 mutation steps between the present study and S. africana (FN431674, FN431680-82, FN431684, FN431688) from South African east coast (Stelbrink et al, 2010) (Fig. 2).…”
Section: Unfringed Barbels Unfringed Barbels Unfringed Barbelsmentioning
confidence: 56%
See 1 more Smart Citation
“…From this study we observed that the inter-specific divergence varied from 7.4 to 10.8% in Squatina with a minimum intraspecific distance of 1.3% in S. africana. The neighbor joining network showed 8 and 9 mutation steps between the present sample (KY497255) and S. africana (HQ945896 and HQ945905) from Tugela Deep (Steinke et al, 2016) and 15 mutation steps between the present study and S. africana (FN431674, FN431680-82, FN431684, FN431688) from South African east coast (Stelbrink et al, 2010) (Fig. 2).…”
Section: Unfringed Barbels Unfringed Barbels Unfringed Barbelsmentioning
confidence: 56%
“…Pair-wise genetic distances (Kimura 2 parameter) based on COI sequences from Squatina spp. (FN431752) and S. californica (FN431717) (Ward et al, 2008;Stelbrink et al, 2009;Moftah et al, 2011;Steinke et al, 2016). The pairwise genetic distance value (k2p) based on COI sequences were given in Table 2.…”
Section: Unfringed Barbels Unfringed Barbels Unfringed Barbelsmentioning
confidence: 99%
“…At CBG 650bp of the mitochondrial COI region were obtained by following standardized high-throughput protocols for DNA barcode amplification and sequencing [81]. At UNIBO the same COI fragment was amplified using the primer set FishF2 and FishR2 following the protocol described in Ward et al [82].…”
Section: Methodsmentioning
confidence: 99%
“…Firstly, it is providing an increasingly effective identification 'service' for groups with a well-parametrized barcode reference library. Secondly, it is accelerating taxonomic progress by aiding the recognition of species and by facilitating the connection of their life stages [100] and sexes [101], associations that are often challenging without barcode data. For example, more than half of all genera of phorid flies are only known from one sex [102], creating high risk for synonymy.…”
Section: Impacts Of Dna Barcodingmentioning
confidence: 99%